Diurnal emotional reactivity: Ultradian changes at neural and behavioral levels in men. (June 2015) - Hot, Pascal; Sequeira, Henrique
<x xml:space="preserve">Abstract</x> The aim of this study was to examine the ultradian dynamic of emotional processing in men. Event-related potentials were recorded while participants watched different sets of unpleasant and neutral pictures every 15 min for 3 h. Emotional feelings induced by unpleasant pictures were also assessed with self-rating scales at the end of each picture set. Whereas brain processing of neutral pictures remained stable over time, a late positive component elicited by unpleasant pictures presented ultradian oscillations varying between 65 and 110 min in 77% of the participants, mainly in the right centro-posterior area. Ultradian rhythms were also observed for values self-rating the intensity of unpleasant feelings. Correlative analyses performed between brain and behavioral ultradian oscillations indicated that these rhythms follow a temporal opposite pattern. For the first time, these results raise questions regarding the modulating role of ultradian oscillations when the brain computes the significance of unpleasant stimuli and produces the final emotional feelings. Overall, these findings open new perspectives on the temporal regulation of emotional reactivity in healthy individuals and in those with affective disorders.